Feller Property for a Special Hybrid Jump-Diffusion Model - Jinying Tong (Abstract and Applied Analysis)
We consider the stochastic stability for a hybrid jump-diffusion model, where the switching here is a phase semi-Markovian process. We first transform the process into a corresponding jump-diffusion with Markovian switching by the supplementary variable technique. Then we prove the Feller and strong Feller properties of the model under some assumptions.